Effect of urban function and landscape structure on the urban heat island phenomenon in Beijing, China - Yao, Lei; Xu, Ying; Zhang, Baolei (Landscape and ecological engineering, 2019)
Rapid urbanization has aggravated the urban thermal risk and highlighted the urban heat island (UHI) effect. To improve understanding on the effect of urbanization on the UHI effect, it is essential to determine the relationship between the UHI effect and the complexities of urban function and landscape structure. For this purpose, 5116 urban function zones (UFZs), representing the basic function units of urban planning, were identified in Beijing. Land cover and land surface temperature (LST) values were extracted based on remote sensing data. UFZ, land cover, and LST were used to represent the urban function, landscape, and UHI characteristics, respectively. Then, the effects of urban function and landscape structure on the UHI effect were examined. The results indicated that the urban thermal environment exhibited obvious spatiotemporal heterogeneity due to the variation of urban function and landscape complexity: (1) UFZs showed significantly different LST characteristics for different functions and seasons, and the mean LST gap among different types of UFZ can reach 1.72–3.85 °C. (2) During warm seasons, the UHI region is mainly composed of residential, industrial, and commercial zones, while recreational zones contribute as an important UHI source region during cold seasons. (3) Urban developed land and forest are the most important landscape factors contributing to the UFZ effect in the urban thermal environment. These findings have useful implications for urban landscape zoning to mitigate the UHI effect.